2000
DOI: 10.1046/j.1365-2796.2000.00582.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered bone metabolism in inflammatory bowel disease: there is a difference between Crohn’s disease and ulcerative colitis

Abstract: Abstract. Ardizzone S, Bollani S, Bettica P, Bevilacqua M, Molteni P, Bianchi Porro G (`L. Sacco' University-Hospital, Milan, Italy). Altered bone metabolism in inflammatory bowel disease: there is a difference between Crohn's disease and ulcerative colitis. J Intern Med 2000; 247: 63±70.Objectives. The aims of this study were to assess bone metabolism in inflammatory bowel disease (IBD) patients and to evaluate potential differences between Crohn's disease (CD) and ulcerative colitis (UC) with respect to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
142
6
12

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(175 citation statements)
references
References 26 publications
10
142
6
12
Order By: Relevance
“…Moreover, BMD was found to be low despite normal serum 25OHD concentration in many studies of patients with IBD. 33,34,50,51 We found no significant association between serum 25OHD concentration and zLSBMD among our subjects, although there was a high prevalence of low zLSBMD. We selected a time interval of 6 months before or after BMD measurement to assess the vitamin D status of our patients, because our goal was to capture in a cross-sectional manner a serum 25OHD concentration that would be most representative and reflective of the vitamin D status of the patients around the time of their BMD measurement.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Moreover, BMD was found to be low despite normal serum 25OHD concentration in many studies of patients with IBD. 33,34,50,51 We found no significant association between serum 25OHD concentration and zLSBMD among our subjects, although there was a high prevalence of low zLSBMD. We selected a time interval of 6 months before or after BMD measurement to assess the vitamin D status of our patients, because our goal was to capture in a cross-sectional manner a serum 25OHD concentration that would be most representative and reflective of the vitamin D status of the patients around the time of their BMD measurement.…”
Section: Discussioncontrasting
confidence: 72%
“…29 Fewer studies have described the vitamin D status of adults with UC compared with those with CD. Serum 25OHD concentrations have been found to be normal in some studies of patients with UC, 33,34 whereas others report serum 25OHD concentrations <12 ng/mL in 15%. 25 In one study, 22 the serum 25OHD concentration was <10 ng/mL in 45% of adult patients with UC and was not different from that in patients with CD.…”
Section: Introductionmentioning
confidence: 98%
“…This may be due to malabsorption, particularly in CD patients who have undergone surgical resection of the small bowel. However, other studies, including ours, have shown little or no difference between UC and CD patients [11] [12]. Unlike previous studies, we found that age, prior fracture, disease duration, disease-associated inflammation, and smoking were not associated with bone loss.…”
Section: Discussioncontrasting
confidence: 99%
“…Estimates of osteopenia in IBD range from 31 to 59% and osteoporosis from 5 to 41%. Various studies exploring the cause of low BMD in IBD found a significant correlation between glucocorticoid treatment and decreased BMD (3,5,17,28,29). Glucocorticoids, such as prednisolone, are wellknown drugs for their potent anti-inflammatory and immunosuppressive properties.…”
mentioning
confidence: 99%